2016
DOI: 10.1371/journal.pone.0154493
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Intra-Community Microbial Interaction Patterns from Metagenomic Datasets Using Associative Rule Mining Techniques

Abstract: The nature of inter-microbial metabolic interactions defines the stability of microbial communities residing in any ecological niche. Deciphering these interaction patterns is crucial for understanding the mode/mechanism(s) through which an individual microbial community transitions from one state to another (e.g. from a healthy to a diseased state). Statistical correlation techniques have been traditionally employed for mining microbial interaction patterns from taxonomic abundance data corresponding to a giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In this case, the interaction between A and B or A and C is nonexistent until the arrival of the third species, which can be seen as an extreme case of interaction modification. Although a few association rules involving more than two microbial taxa have been reported previously [31], it is not clear whether these are due to overfitting (a challenge for all HOI inference algorithms), environmental factors, combinations of pair-wise associations, or true HOIs. Finally, visualizing HOIs is not trivial and requires hypergraphs, i.e., networks where an edge connects more than two nodes.…”
Section: Challenge #5: What About Higher-order Interactions (Hois)?mentioning
confidence: 99%
“…In this case, the interaction between A and B or A and C is nonexistent until the arrival of the third species, which can be seen as an extreme case of interaction modification. Although a few association rules involving more than two microbial taxa have been reported previously [31], it is not clear whether these are due to overfitting (a challenge for all HOI inference algorithms), environmental factors, combinations of pair-wise associations, or true HOIs. Finally, visualizing HOIs is not trivial and requires hypergraphs, i.e., networks where an edge connects more than two nodes.…”
Section: Challenge #5: What About Higher-order Interactions (Hois)?mentioning
confidence: 99%
“…While the interaction patterns in microbial communities can be predicted using metagenomic datasets and mathematical simulations (Freilich et al ., 2011; Tandon et al ., 2016), studying cultivable microbial interactions can provide direct insights into complex communities. By comparing the productivity of species mixtures to that of each species alone, Foster and Bell found that competition, rather than cooperation, is prevalent among culturable bacterial species isolated from aquatic environments (Foster and Bell, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Bayesian approaches are powerful, because they provide principled estimates of uncertainty throughout the model, which is an especially important feature in biomedical applications where noisy inputs are the norm. We note that another rule-based method, association rule mining (ARM), has recently been applied to analyzing microbiome data in a different context (finding interaction patterns among OTUs) [14]. Although ARM has some commonalities with Bayesian rule learning approaches, ARM methods tend to employ user-based cutoffs and heuristics, rather than principled probabilistic methods, as their primary function is to mine large databases for putative interactions, rather than build predictive models.…”
Section: Introductionmentioning
confidence: 99%